2017
DOI: 10.3390/ijerph14101101
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction among Health-Care Staff in Township Health Centers in Rural China: Results from a Latent Class Analysis

Abstract: Background: The lower job satisfaction of health-care staff will lead to more brain drain, worse work performance, and poorer health-care outcomes. The aim of this study was to identify patterns of job satisfaction among health-care staff in rural China, and to investigate the association between the latent clusters and health-care staff’s personal and professional features; Methods: We selected 12 items of five-point Likert scale questions to measure job satisfaction. A latent-class analysis was performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 31 publications
(40 reference statements)
6
28
0
1
Order By: Relevance
“…As for the risk of bias, more than half of the included studies presented a low risk of bias, with the total score ranging from 6 points to 10 points (in online supplementary appendix 3). Included studies analysed the motivation of PCWs from different perspectives: some measured job satisfaction15–30; some explored the motivating factors’ influence on attrition and retention18 22 31–35; some studied the impact of some policies or interventions on the motivating factors for health workers 31 36–46…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the risk of bias, more than half of the included studies presented a low risk of bias, with the total score ranging from 6 points to 10 points (in online supplementary appendix 3). Included studies analysed the motivation of PCWs from different perspectives: some measured job satisfaction15–30; some explored the motivating factors’ influence on attrition and retention18 22 31–35; some studied the impact of some policies or interventions on the motivating factors for health workers 31 36–46…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen out of the 36 articles reported the factor of career advancement (table 1), which was considered as the one of top three contributors to satisfaction 15 16 19 20 22 23 29. The gap between the expected and actual professional development was one of the main sources of job dissatisfaction 17.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…is related to healthcare service quality and outcomes. Low satisfaction is a major cause of psychological and social stress in medical staff and correspondingly of employee turnover [ 2 , 3 , 4 , 5 ]. Many studies have demonstrated that healthcare staff with high satisfaction provide higher quality medical services, resulting in better healthcare outcomes and higher patient satisfaction [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the healthcare system, the job satisfaction of physicians is in the interest of the entire healthcare context (DeVoe et al, 2002) and has important eff ects on physician productivity, the quality of medical care, and the supply of physicians available to meet the medical care needs of population (Malik et al, 2010). Conversely, a lower healthcare staff job satisfaction will lead to increased brain drain, poor work performance and lower healthcare outcomes (Wang et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%